Model Struktural Faktor-Faktor Berpengaruh Terhadap Kinerja Badan Usaha Milik Desa di Kabupaten Jembrana, Bali - G K Gandhiadi; I Putu Eka N Kencana (Jurnal Matematika, 2020)
One of the efforts to develop the rural economy is the establishment of economic institutions such as Village-Owned Enterprises (BUMDes) which are supported by the role of the local government and are based on the wishes of the village community. This BUMDes is expected to be able to increase market demand based on proper management of the existing village potential. Through cooperative behavior (social capital), synergy and a good entrepreneurial orientation in BUMDes managers and the positive role of the government it is hoped that there will be an increase in BUMDes business performance in Jembrana Regency.